Atypical rotavirus among diarrhoeic children living in Belém, Brazil Rotavírus atípicos detectados em crianças diarréicas, em Belém, Brasil - Yvone B. Gabbay; Joana D'Arc P. Mascarenhas; Alexadre C. Linhares; Ronaldo B. Freitas (Memorias do Instituto Oswaldo Cruz, 1989)
Atypical rotaviruses were detected in faeces from two diarrhoeic children living in Belém, Pará, Brazil. Rotavirus particles were detected by electron microscopy and the RNA electrophoresis showed patterns which were compatible with group C rotaviruses. Tests for the presence of group A antigen by enzyme-linked-immunosorbent assay (ELISA) were negative. The two children had three successive rotavirus infection and in both cases the atypical strains were excreted at the time of the third infection, causing a mild and short-lasting disease. Rotavírus atípicos foram detectados nas fezes de duas crianças diarreícas residentes em Belém, Brasil. Partículas de rotavírus foram visualizadas por microscopia eletrônica nos espécimes fecais de ambos os pacientes, tendo a eletroforese do ácido ribonucleico (ARN) exibido padrões compatíveis com rotavírus do grupo C. Testes imunoenzimáticos (ELISA) foram negativos quanto à presença de antígenos do grupo A. As duas crianças apresentaram três infecções sucessivas por esse agente, sendo que, em ambos os casos, os rotavírus atípicos foram excretados por ocasião da terceira infecção, produzindo sintomas brandos e de pouca duração.